Common pathogen-associated molecular patterns induce the hyper-activation of NLRP3 inflammasome in circulating B lymphocytes of HIV-infected individuals. (1st May 2021) - Leal, Vinícius Nunes Cordeiro; Reis, Edione Cristina; Fernandes, Fernanda Pereira; Soares, Jaíne Lima da Silva; Oliveira, Iohanã Gabriely Costa; Souza de Lima, Dhêmerson; Lara, Amanda Nazareth; Lopes, Marta Heloísa; Pontillo, Alessandra
Abstract : Objective: Despite the antiretroviral treatment, people with HIV (PWH) still experience systemic chronic inflammation and immune-senescence, which represent risk factors for severe comorbidities and inefficient response to pathogens and vaccines. Given the dysregulation of NLRP3 inflammasome in PWH and the recently demonstrated role played by NLRP3 in B lymphocytes, we hypothesized that NLRP3 dysregulation in B cells can contribute to chronic inflammation and humoral dysfunction in PWH. Design: NLRP3 inflammasome activation was evaluated in B lymphocytes and correlated with antibodies production and immunization response in PWH. Methods: NLRP3 inflammasome activation was compared in B lymphocytes isolated from PWH and healthy donors, in resting and stimulated conditions. Functional polymorphic variants in NLRP3 and IL1B genes were analysed in a cohort of PWH submitted to anti-HBV vaccine to assess the effect of NLRP3 inflammasome on humoral response. Results: The NLRP3 inflammasome activation in response to common PAMPs (LPS, ß-glucan) resulted higher in B lymphocytes of PWH than in HD. CpG-induced IgM secretion was also increased in B cells of PWH. NLRP3, but not IL1B, gain-of-function polymorphism associated to anti-HBs levels. Conclusion: These data reveal the dysregulation of NLRP3 inflammasome in B lymphocytes of PWH. Differently from myeloid compartment, which present an exhausted NLRP3 inflammasome, the complex appears to be hyper-activated in B cells of PWH, likely contributing to chronic inflammation and affecting humoral response. Abstract : Supplemental Digital Content is available in the text